A Novel Plant Leaf Patch Absorbed With IL-33 Antibody Decreases Venous Neointimal hyperplasia - Xie, Boao; Bai, Xiche; Sun, Peng; Zhang, Liwei; Wei, Shunbo; Bai, Hualong (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: We recently showed decellularized leaf scaffold can be loaded with polylactic-co-glycolic acid (PLGA)-based rapamycin nanoparticles, this leaf patch can inhibit venous neointimal hyperplasia in a rat inferior vena cava (IVC) venoplasty model. IL-33 plays a role in the neointimal formation after vascular injury. We hypothesized that plant leaf can absorb therapeutic drug solution and can be used as a patch with drug delivery capability, and plant leaf absorbed with IL-33 antibody can decrease venous neointimal hyperplasia in the rat IVC venoplasty model. Method: Human spiral saphenous vein (SVG) graft implanted in popliteal vein was harvest from a patient with trauma and analyzed by immunofluorescence. Male Sprague-Dawley rats (aged 6-8 weeks) were used to create IVC patch venoplasty model . Plant leaf absorbed with rhodamine, distilled water (control), rapamycin, IL-33, IL-33 antibody was cut into patches (3 x 1.5 mm2) and were implanted to the rat IVC. Patches were explanted at day 14 for analysis. Result: At day 14, in the patch absorbed with rhodamine group, immunofluorescence showed the rhodamine fluorescence in the neointima, inside the patch and in the adventitia. There was a significantly thinner neointima in the plant patch absorbed with rapamycin (p=0.0231) compared to the patch absorbed with distilled water. There were a significantly large number of IL-33 (p=0.006) and IL-1β (p=0.012) positive cells in the human SVG neointima compared to human great saphenous vein. In rats, there was a significantly thinner neointima, smaller number IL-33 (p=0.0006) and IL-1β (p=0.0008) positive cells in the IL-33 antibody absorbed patch group compared to the IL-33 absorbed patch group. Conclusion: We found that by using the nature absorption capability of plant leaf, it can absorb drug solution efficiently, it can also be used as a novel drug delivery system and venous patch. IL-33 plays a role in the venous neointimal hyperplasia both in human and rat, neutralization of IL-33 by IL-33 antibody can be a therapeutic method to decrease venous neointimal hyperplasia.